02 NEW ONSET AUTOIMMUNE DISORDERS, PRIMARILY PSORIASIS, IN ANTI-TNF BIOLOGIC EXPOSED PEDIATRIC PATIENTS – THE DEVELOP EXPERIENCE. (7th February 2019) - Colletti, Richard; Griffiths, Anne; Veereman, Gigi; Escher, Johanna; Izanec, James; Busse, Christopher; Wang, Yanli; Gold, Benjamin
Abstract: Background: DEVELOP is a multicenter, prospective, observational registry of the long-term safety and clinical outcomes of 6070 pediatric patients with inflammatory bowel disease (IBD; Crohn's disease, ulcerative colitis, or indeterminate colitis) treated with anti-tumor necrosis factor biologics (aTNF) and/or other medical therapies for IBD as part of routine clinical care. DEVELOP has sites in the United States, Canada and the European Union (EU). Our aim was to characterize the incidence of new autoimmune disorders in a pediatric IBD population exposed to aTNF compared to a population exposed only to non-biologics. Methods: Physicians participating in the registry prescribe IBD treatments based on their usual clinical practice and standards of care. Patients are categorized into cohorts according to their prevalent or incident medication exposure, including patients receiving therapy prior to enrollment and/or during registry follow-up. The most recent available data cut (June 30 2018) includes 21083 patient-years (PY) of follow up in the aTNF cohort and 11277 PY in the non-biologics cohort. Investigators record all new autoimmune disorders in the study database during biannual visits. Results: Among all IBD patients, the incidence of all new autoimmune disorders was statistically significantly greater in the aTNF cohort (0.99 events/100 PY) than the nonbiologics cohort (0.27 events/100 PY) (Table 1). These results were driven by new-onset psoriasis (0.58 events/100 PY), the most frequently reported new autoimmune disorder in the aTNF cohort compared to 0.02 new psoriasis events/100 PY in the non-biologics cohort. The incidence of serious new autoimmune disorders was low in both the aTNF cohort (0.20 events/100 PY) and the non-biologics cohort (0.07 events/100 PY). In the aTNF cohort, serious new autoimmune disorders by preferred term that occurred more than once included the following: Psoriasis (0.06 events per 100 PY, n=12 events), Sclerosing Cholangitis (0.02 events per 100 PY, n=4) Lupus-like syndrome (0.02 events per 100 PY, n=4) Optic neuritis (0.01 events per 100 PY, n=3), Autoimmune hepatitis (0.01 events per 100 PY, n=3) In the non-biologics cohort, there were no reports of serious adverse events of psoriasis, optic neuritis, or lupus-like syndrome, one report (0.01 events/100 PY) each of serious autoimmune hepatitis and juvenile idiopathic arthritis and two cases of sclerosing cholangitis (0.02 events/100 PY). Conclusion: New autoimmune disorders were noted approximately once every 100 patient years in the aTNF cohort and were significantly more common compared to the non-biologic cohort. New serious autoimmune disorders in the aTNF cohort were uncommon, with only 0.20 new events per 100 PY. New autoimmune disorders do arise in aTNF treated pediatric IBD patients but overall are uncommon and not serious.